Influence of fullerene photodimerization on the PCBM crystallization in polymer: Fullerene bulk heterojunctions under thermal stress. Issue 16 (20th June 2013) - Piersimoni, Fortunato; Degutis, Giedrius; Bertho, Sabine; Vandewal, Koen; Spoltore, Donato; Vangerven, Tim; Drijkoningen, Jeroen; Van Bael, Marlies K.; Hardy, An; D'Haen, Jan; Maes, Wouter; Vanderzande, Dirk; et al.
ABSTRACT For an increased lifetime of polymer:fullerene bulk heterojunction (BHJ) solar cells, an understanding of the chemical and morphological degradation phenomena taking place under operational conditions is crucial. Phase separation between polymer and fullerene induced by thermal stress has been pointed out as a major issue to overcome. While often the effect of thermal stress on the morphology of polymer:fullerene BHJ is investigated in the darkness, here we observe that light exposure slows down fullerene crystallization and phase separation induced at elevated temperatures. The observed photo‐stabilizing effect on active layer morphology is quite independent on the polymer and is attributed to light‐induced dimerization of the fullerene. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2013, 51, 1209–1214